2019
DOI: 10.1002/smll.201902321
|View full text |Cite
|
Sign up to set email alerts
|

Lithiumpyridinyl‐Driven Synthesis of High‐Purity Zero‐Valent Iron Nanoparticles and Their Use in Follow‐Up Reactions

Abstract: The synthesis of zero‐valent iron (Fe(0)) nanoparticles in pyridine using lithium bipyridinyl ([LiBipy]) or lithium pyridinyl ([LiPy]) is presented. FeCl3 is used as the most simple starting material and reduced either in a [LiBipy]‐driven two‐step approach or in a [LiPy]‐driven one‐pot synthesis. High‐quality nanoparticles are obtained with uniform, spherical shape, and mean diameters of 2.9 ± 0.5 nm ([LiBipy]) or 4.1 ± 0.7 nm ([LiPy]). The as‐prepared, high purity Fe(0) nanoparticles are monocrystalline. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…Thus, amido ligands might be interesting to investigate as a new class of ligands for iron based NPs in line with the work reported by Egeberg et al on lithium pyridine stabilized iron NPs. 42 Magnetic measurements, supported by DFT calculations, indicated that size reduction effects were easily counter balanced by surface coordination of amines and hydrides on the surface of the NPs. Hydride titration conrmed the theoretical prediction stating that these are the species responsible for the variations in magnetization observed.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, amido ligands might be interesting to investigate as a new class of ligands for iron based NPs in line with the work reported by Egeberg et al on lithium pyridine stabilized iron NPs. 42 Magnetic measurements, supported by DFT calculations, indicated that size reduction effects were easily counter balanced by surface coordination of amines and hydrides on the surface of the NPs. Hydride titration conrmed the theoretical prediction stating that these are the species responsible for the variations in magnetization observed.…”
Section: Discussionmentioning
confidence: 92%
“… Exemplary coordination compounds and structures obtained by follow‐up reactions using reactive base‐metal nanoparticles as starting materials: ∞ 1 [FeI 2 (CH 3 OH) 2 ], [FeI 2 (PPh 3 ) 2 ], [Tm 5 O(C 3 H 7 O) 13 ], [Fe(Cp*) 2 ], and [Sm 6 O 4 (cbz) 10 (thf) 6 ] ⋅ 2 C 7 H 8 (H atoms omitted for clarity, modified reproduction from [16c,18] ). …”
Section: Resultsmentioning
confidence: 99%
“…Especially powder samples of the nanosized metals show violent reactions with air or water, which are comparable or even more violent than known for bulk alkali metals. In the liquid phase under inert atmosphere, however, the reactivity and reactions can be well‐controlled and, for instance, result in bimetallic nanoparticles as well as metal‐oxide and metal‐sulfide nanoparticles or single‐crystalline metal iodides and metal alkoxides [16b‐d] . Moreover, the base‐metal nanoparticles offer the option to prepare coordination compounds in the liquid phase at mild conditions (20–100 °C) (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 程度, 并提供定向的电荷传导路径 [42][43][44] 。 因此, 近年 来纳米铁颗粒负载于多孔/介孔纳米材料(Porous/ mesoporous materials, 如介孔 C, SiO 2 , Al 2 O 3 , TiO 2 等) 的载体界面设计被广泛用于环境修复, 如电催化还 原硝酸根 [45][46] 。目前, 非对称纳米结构和纳米颗粒 载体界面组装设计用于优化和实现纳米铁颗粒活性暴 露位点的精确调控, 增加复合材料中的金属含量 [47][48][49] [50] , (B)具有核壳结构的 Fe 纳米粒子 [51] , (C)硼氢化钠还原 Fe 3+ 为纳米铁颗粒 [52] , (D)有机还原剂两步还原铁离子为纳米铁颗粒 [55] Fig. 2 (A) Liquid nitrogen activation of ZVI [50] , (B) HRTEM images showing three types of Fe nanoparticles with core-shell structure [51] , (C) sodium borohydride being introduced to reduce Fe 3+ to ZVI [52] , (D) illustration of the [LiBipy]-driven two-step synthesis: formation of [LiBipy] radical by coupling reaction [55] 成 2~100 nm 的单分散纳米铁颗粒。通过石英微天 平, 沉积速率可调控至 10 mg/h。用 TEM 可观察到 α-Fe 相的外层形成了一层铁氧化物。 [54] 。Feldmann 等 [55] [56] 。 但 是, 该方法制备成本较高, 并且制备的新鲜纳米铁颗 无 机 材 料 学 报 第 36 卷 图 3 (A-a)胶囊状核壳结构 Fe/C@mSiO 2 的制备示意图 [58] , (A-b)用溶胶-凝胶和原位热还原法构建蛋黄结构 Fe 0 @mC 的制备示意图 [47] , (A-c)分层蛋黄结构 Fe@SiO 2 /Ni 的制备路线图 [59] , (B)Janus 结构的 Fe@PMO 的合成示意图 [48] , (C)类山莓状 CL-Fe@C 的合成示意 图 [49] , (D-a) 纳米复合材料 nZVI @OMC 的合成路线图 [46] , (D-b)纳米铁颗粒负载于介孔碳(nZVI@C)的合成示意图 [65] Fig. 3 (A-a) Schematic illustration of the small iron nanoparticles in a capsule (Fe/C@mSiO 2 ) [58] , (A-b) schematic illustration of the Sol-Gel coating process and in-situ confined thermally reduction strategy for the fabrication of the porous carbon capsulated Fe 0 yolk-shell nanospheres (Fe 0 @mC) [47] , (A-c) illustration of the synthesis of hierarchical yolk-shell Fe@SiO 2 /Ni nanocomposites [59] , (B) schematic illustration of the synthetic procedure for Fe@PMO with Janus structure [48] , (C) schematic illustration of in situ confined thermal reduction strategy for preparation of corchorifolius-like structure carbon-coated Fe microsphe...…”
unclassified